Ecological Education in Primary School Settings: A Bibliometric Analysis - Abbadi Said Thalib; Rsaldi Hendro Koestoer (CV. Publikasi Indonesia, 2025)
This research uses quantitative bibliometric analysis and qualitative content analysis of 30 studies indexed by Scopus. This research provides a complete picture of trends and progress in environmental education for children studying in primary school. The bibliometric study, conducted from 2019 to 2024, mapped trends, leading authors, and dominant research topics using VOS Viewer software. This research aims to increase stakeholders' attention to outdoor experiences and learning. Hands-on ecological education in nature, cooking experiences, and incorporating ecological topics into language teaching are common pedagogical techniques found in content analysis. Meanwhile, problems such as lack of resources, teacher preparation, and mismatch between outdoor and classroom activities hinder effective implementation. This study also shows that environmental education benefits students' environmental awareness and pro-environmental behavior by emphasizing the importance of greater resources, increasing teacher support, and incorporating sustainability goals into the curriculum.